The Effect of Brand Image and Service Quality with Word of Mouth on The Decision to Stay at Swiss-Belhotel Borneo in Samarinda - Rachel Novia Atan (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Brand Image and Quality Service with Word of Mouth are important applied by service company in the hotel sector who wants to increase the number of guests to use or stay at the hotel. Swiss-Belhotel Borneo in Samarinda is one of the service companies in the hotel sector that depends on the number of guests who decide to stay at the hotel in order to make a profit. However, the number of guests who decide to stay at a hotel has not yet reached the target set and even the percentage of guests has fluctuated. This study aims to determine the effect of Brand Image, Service Quality, and Word of Mouth on the decision to stay at Swiss-Belhotel Borneo in Samarinda. The variables used in this study consisted of independent variables are brand image, service quality, and word of mouth, while the dependent variable was the stay decision. The population in this study are guests who are staying or have stayed at Swiss-Belhotel Borneo in Samarinda. Therefore, sampling was conducted for this study. The sample in this study was 100 respondens. The sampling technique in this study was conducted with non-probability sampling. The type of non-probability sampling used is accidental sampling. Data collection methods using a questionnaire. The analysis technique used is multiple linear regression analysis. The result of the showed that brand image, service quality, and word of mouth had a positive and significant effect on the decision to stay. Hypothesis testing as a whole proves the hypothesis influential and significant on the decision to stay together is accepted (Ho rejected and Ha accepted). The results of the t Test found that Word of Mouth variable was the most significant variable and had a positive influence on the decision to stay at Swiss-Belhotel Borneo in Samarinda.